PI3K-Alpha Plays A Major Role In Multiple Myeloma and Its Inhibition With BYL917 Decreases Proliferation, Synergizes With Other Therapies and Overcomes Stroma-Induced Resistance - Azab, Feda; Vali, Shireen; Potter, Nicholas; Abraham, Joseph; Muz, Barbara; De La Puente, Pilar; Abbasi, Taher; Vij, Ravi; Azab, Abdel Kareem (Blood, 2013)
Multiple myeloma (MM) is the second most prevalent hematologic malignancy and is still incurable. The PI3K pathway is activated and correlated with drug resistance in MM. Pan-inhibition of the PI3K pathway resulted in serious side effects, therefore, we focused on specific inhibition of the PI3K-alpha isoform. We investigated the role of PI3K- alpha in the progression and drug resistance of MM, by inhibiting the PI3K- alpha with a novel specific inhibitor BYL719. This is the first study to describe the preclinical effect of BYL719 on MM in particular and in hematologic malignancies in general. We analyzed the gene expression of PI3K isoforms in MM patients based on published datasets from the Gene Expression Omnibus by Zhan et al and found that PI3K-alpha and beta isoforms were highly expressed in MM. However, the fold-change of expression of the alpha isoform in MM patients was higher than the beta isoform, compared to healthy subjects. BYL719 inhibited the survival of MM cells isolated from three MM patients by MTT, at an IC50 around 1uM, but had no effect on normal PBMCs. Furthermore, BYL719 inhibited survival of all MM cell lines in a different manner. In silico-predicted activity of PI3K-alpha in the cell lines was exponentially correlated with the killing induced by the PI3K inhibitor BYL719 in vitro. BYL719 significantly decreased the activation of the PI3K signaling related proteins (pAKT, pS6R, and pGSK) by western blotting. Moreover, BYL719 inhibited cell cycle of MM cells detected by PI staining showed induction of G1-phase cell cycle arrest. BYL719 inhibited MM proliferation of MM1s cells in a dose dependent manner, through decreasing the levels of pCyclin-E1 and pRb, and increasing of P27 levels. The results were in agreement with the in silico studies that predicted the inhibition of other cell-cycle proteins including CDK4-Cyclin D complex, Myc-Max complex and CDK1-Cyclin B complex by BYL719 in a dose dependent manner. Moreover, BYL719 (0-2.5uM) increased the fraction of apoptotic MM cells in a dose depended manner, as detected by Annexin/PI staining. BYL719 induced apoptosis signaling by inducing the cleavage of Caspase-3, Caspase-9 and PARP by western blotting, in a dose dependent manner. We tested the effect of the combination of BYL719 with other drugs (Bortezomib and Carfilzomib) on survival of MM cells by MTT. We found that the combination of the two drugs decreased the surviving fraction of MM cells more than each of the drugs alone. Mechanistically, Bortezomib increased pAKT and pS6R as a resistance mechanism, and BYL719 abolished the Bortezomib-induced increase of pAKT and pS6R. Moreover, BYL719 enhanced the activation of pJNK induced by Carfilzomib and the combination of each drug increased cleavage of PARP, caspase-3 and caspase-9 more than each of the drugs alone. We tested the effect of BYL719 on the interaction of MM cells with BM stromal cells (BMSCs), and it was found that BYL719 decreased the adhesion of MM cells to BMSCs in a dose-dependent manner. Mechanistically, BYL719 decreased the activation of adhesion signaling such as pFAK, pSRC and pCofilin in a dose dependent manner. The in silico studies predicted the inhibition of the small GTPases Rho, Rac and Cdc42. To test the effect of BYL719 on drug resistance induced by the BM stroma, MM cells were co-Cultured with BMSCs, treated with BYL719 in combination with Bortezomib or Carfilzomib. It was found that co-culture with BMSCs increased the surviving fraction of MM cells after treatment with Bortezomib and Carfilzomib, as a drug resistance mechanism. The combination of the two drugs with BYL719 overcame the resistance induced by the stroma and reduced the surviving fraction to the values observed for treatment without presence of stroma. This is the first study to describe preclinical effect of BYL719 on MM in particular and hematologic malignancies in general. The PI3K-alpha isoform plays a major role in the progression and drug resistance in MM cells, and it's inhibition with BYL719 reduces proliferation, inhibits cell cycle and induces apoptosis in MM cells. Moreover, it showed that BYL719 synergizes with Bortezomib and Carfilzomib, and overcomes drug resistance induced by BM stroma. Our findings provide a preclinical basis of future clinical trial of BYL719 in MM as a single agent or in combination with other drugs. Vali:Cellworks Group Inc., San Jose, CA, USA: Employment. Abbasi:Cellworks Group Inc: Employment.